THE EFFECT OF GROUP INVESTIGATION TECHNIQUE ON THE STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXTS - Fahrunnisa Mariyam; Johan Sinulingga (Universitas Negeri Medan, 2015)
This is an attempt to discover the effect of applying the Group Investigation Technique on the students’ achievement in writing descriptive texts. It was conducted by using experimental research design. The population of this research was the second (VIII) grade students of SMPS Dharma Patra Pangkalan Berandan. There were one- hundred and ninety students involved as the population. Which consists of five parallel classes, two classes out of five classes was chosen as the sample by using lottery technique namely experimental and control group. The result was class VIII-A consisted of 15 students became the experimental group and class VIII-B consisted of 15 students became the control group. The experimental group was taught by using Group Investigation Technique while the control group was taught by do not using the treatment. The instrument for collecting the data was writing test. The data were analyzed by using t-test formula. The result shows that the value of t-observed (5,85) is higher than the value of t-table (2.048) ( α = 0.05 ) with the degree of freedom (df) = 28. It means that there is a significant effect of applying Group Investigation Technique on the students’ achievement in writing descriptive texts. So, the alternative hypothesis (Ha) is accepted.